Correlation Between Students’ Learning Habit in Listening English Song and Their Pronunciation Capacity - Rahmawati Upa; Tenri Ola; Edi Wahyono (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This research aimed at finding whether or not students’ habit of listening to English songs (X variable) and their pronunciation ability(Y variable) have correlation. It was conducted at SMA Negeri 3 Palopo. The sample taken was 30 students in academic year 2020/2021. The method used in this research was quantitative method with the correlational design. The instruments used to gather the data were questionnaire and pronunciation test. The scores from both instruments were calculated and analyzed by using SPSS to see whether there was a correlation between the two variables or not. The result showed that there was a correlation, with the index value of correlation coefficient (rxy) of 0.442 which meant there was a moderate correlation. Furthermore, the hypothesis testing showed that the index value of correlation coefficient (rxy) of 0,442 was higher than the index value of correlation coefficient of the Product Moment table (rt) of 0,306 which meant that the null hypothesis (H0) was rejected and alternative hypothesis (H1) was accepted. In conclusion, there was a moderate significance correlation between the two variables. Based on the findings mentioned above, the researcher assumes that the more students listening to English song the more their listening ability will be better. It means listening to English song can be used as media to improve students’ listening ability. Therefore, the researchers suggest that the English teacher could use movie as a media in language teaching in improving students’ listening skill.